Peningkatan Pemahaman Konsep Matematika Siswa SMP melalui Model Pembelajaran Kooperatif Tipe Jigsaw - Ari Septian; Citra Laila Ramadhanty (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to determine the increase in students' understanding of mathematical concept skills, student activities, and to determine student responses to learning by using a Jigsaw type cooperative learning model. This learning can foster collaboration so that there is good interaction between students and the appreciation at the end of learning can foster student motivation to be more serious in learning. The method used in this research is classroom action research (CAR). This research was conducted in SMP Negeri 1 Cilaku VII E students, amounting to 35 people. The instruments used in this study were test cycles I, II and III, journals, questionnaires, teacher and student observation sheets. Based on the results of the study it was found that The ability to understand students' mathematical concepts increases with the progress of learning by using a Jigsaw cooperative model, Increased learning activities of teachers and students can be seen from the results of observations in each cycle has increased, and the attitude scale results found that students are positive towards mathematics learning by using a Jigsaw cooperative learning model.